Does individualism bring happiness? Negative effects of individualism on interpersonal relationships and happiness - Ogihara, Yuji; Uchida, Yukiko (Frontiers in Psychology, 2014)
We examined the negative effects of individualism in an East Asian culture. Although individualistic systems decrease interpersonal relationships through competition, individualistic values have prevailed in European American cultures. One reason is because individuals could overcome negativity by actively constructing interpersonal relationships. In contrast, people in East Asian cultures do not have such strategies to overcome the negative impact of individualistic systems, leading to decreased well-being. To test this hypothesis, we investigated the relationship between individualistic values, number of close friends, and subjective well-being (SWB). Study 1 indicated that individualistic values were negatively related with the number of close friends and SWB for Japanese college students but not for American college students. Moreover, Study 2 showed that even in an individualistic workplace in Japan, individualistic values were negatively related with the number of close friends and SWB. We discuss how cultural change toward increasing individualism might affect interpersonal relationships and well-being.